Pharmacogenetic model of retinoic acid-induced dyslipidemia and insulin resistance - Krupková, Michaela; Janků, Michaela; Liška, František; Šedová, Lucie; Kazdová, Ludmila; Křenová, Drahomíra; Křen, Vladimír; Šeda, Ondřej (Pharmacogenomics, 2009)
AIMS: Therapeutic administration of retinoids is often accompanied with undesirable side effects, including an increase in lipid levels in up to 45% of treated patients. We tested the hypothesis of whether spontaneously hypertensive rat (SHR) and congenic SHR.PD-(D8Rat42-D8Arb23)/Cub (SHR-Lx) strains, differing only in a 14-gene region of chromosome 8 and previously shown to display differential sensitivity to the teratogenic effects of retinoic acid, could serve as a pharmacogenetic model set of the metabolic side effects of retinoid therapy. MATERIALS & METHODS: Male, 15-week old rats (n = 12/strain) of SHR and SHR-Lx strains were fed a high-sucrose diet for 2 weeks and subsequently treated either with all-trans retinoic acid (15 mg/kg) or only with a vehicle for 16 days (n = 6/strain/treatment), while still on the high-sucrose diet. We assessed the morphometric and metabolic profiles of all groups, including glucose tolerance tests, levels of insulin, adiponectin, free fatty acids, concentrations of triglycerides and cholesterol in 20 lipoprotein fractions under conditions of both high-sucrose diet and high-sucrose diet plus all-trans retinoic acid administration. RESULTS & CONCLUSION: SHR-Lx displayed substantially greater sensitivity to a number of all-trans retinoic acid-induced metabolic dysregulations compared with SHR, resulting in impairment of glucose tolerance, increased visceral adiposity, and substantially greater increase of circulating triglyceride concentrations, accompanied by a shift towards their less favorable distribution into the lipoprotein fractions. These observations closely mimic the common side effects of retinoid therapy in humans, rendering SHR-Lx an experimental pharmacogenetic model of atRA-induced dyslipidemia.
Keywords: Disease Models, Animal; glukózový toleranční test; Hypertension; Rats, Inbred SHR; zvířata; inzulinová rezistence; zvířata kongenní; sacharosa; Rats; tretinoin; farmakogenetika; Glucose Tolerance Test; modely nemocí na zvířatech; mužské pohlaví; Animals, Congenic; Lipid Metabolism; metabolismus lipidů; Insulin Resistance; Sucrose; Tretinoin; hypertenze; potkani inbrední SHR; krysa rodu Rattus; Dyslipidemias; Animals; Male; dyslipidemie; Pharmacogenetics